Seven‐year experience of enterocutaneous fistula with univariate and multivariate analysis of factors associated with healing: development of a validated scoring system. (18th September 2013) - Rahbour, G.; Gabe, S. M.; Ullah, M. R.; Thomas, G. P.; Al‐Hassi, H. O.; Yassin, N. A.; Tozer, P. J.; Warusavitarne, J.; Vaizey, C. J.
Abstract: Aim: The management of enterocutaneous fistulae (ECF) is complex and challenging. We examined factors associated with fistula healing at a National Intestinal Failure Centre and devised the first scoring system to predict spontaneous fistula healing prior to surgery. Method: A retrospective audit of 177 patients (mean age 48.7 years) treated over 7 years was undertaken. Results were compared with a previously reported series from this unit. Univariate and multivariate analyses wete performed on variables to assess relationship with ECF healing. A scoring system was devised and validated on a prospective cohort. Results: One‐hundred and fifty patients underwent surgery between January 2003 and December 2009. The overall healing rate following surgery in the current series was 94.6% (82% in the previous series). Mean delay from previous surgery to the current operation was 1 year (compared with 8 months previously). Thirty‐day postfistula resection mortality was 0% (compared with 3.5% previously). Twenty‐seven patients underwent medical management alone with overall healing rate of 46.4% ( vs 19.9%). Multivariate analysis revealed that comorbidity ( P  = 0.02), source of referral ( P  = 0.01) and aetiology ( P  = 0.006) had associations with healing. Almost all patients with scores of 0 and 1 healed, whereas the highest scores healed least frequently. Conclusion: Surgical management of ECF is safe and improving. Fistula healing is affected by aetiology, comorbidity and source of referral. The scoring system has the potential to predict ECF healing and can be a useful clinical decision‐making tool.